Cre/CysC ratio may predict muscle composition and is associated with glucose disposal ability and macrovascular disease in patients with type 2 diabetes. Issue 2 (3rd November 2021) - Yang, Qing; Zhang, Mei; Sun, Peng; Li, Yanying; Xu, Huichao; Wang, Kejun; Shen, Hongshan; Ban, Bo; Liu, Fupeng
Abstract : Introduction: Since the ratio of creatinine to cystatin C (Cre/CysC) can reflect muscle volume, it has been proven to be a predictor of sarcopenia in patients with or without diabetes. Here, we investigated the predictive value of Cre/CysC for the skeletal muscle composition and its correlations with glucose disposal ability and diabetic complications in patients with type 2 diabetes. Research design and methods: The skeletal muscle index (SMI) and mean skeletal muscle attenuation (MMA) values of 193 patients with type 2 diabetes were obtained through analyses of CT images at the lumbar 3 level. Results: Serum Cre/CysC was significantly correlated with both the SMI (r=0.375, p<0.001) and MMA (r=0.378, p<0.001). Multiple stepwise linear regression analysis demonstrated that Cre/CysC was the only biochemical predictor of the SMI (β=0.48 (95% CI 0.02 to 0.94)) and MMA (β=0.57 (95% CI 0.14 to 1.01)). Furthermore, the fat mass index (FMI) was significantly associated with the MMA (r=−0.481, p<0.001) but not the SMI (r=0.101, p=0.164). In the diabetic complications analysis, Cre/CysC was significantly lower in patients with cardiovascular disease (95% CI (−1.47 to –0.22), p=0.008) and lower extremity arterial disease (95% CI (−1.44 to –0.29), p=0.004). Moreover, in the 100 g steamed bun test, Cre/CysC was significantly correlated with glucose levels at 60 min (r=−0.162, p=0.045), 120 min (r=−0.287, p<0.001) and 180 min (r=−0.313, p<0.001). Conclusions: Cre/CysC may be a valuable predictor of skeletal muscle composition in type 2 diabetes. Patients with a higher Cre/CysC may have a better ability to dispose of postprandial glucose and are at a lower risk of macrovascular disease.